Protocol for quantifying xenografted human cancer cells in zebrafish larvae using Cellpose - Karina Köpke; Carla-Sophie Lembke; Nynke Oosterhof; Emma S.C. Dijkstra; Judith T.M.L. Paridaen (STAR Protocols)
Summary: Here, we present a protocol for quantifying xenografted human glioblastoma stem cells (GSCs) in zebrafish larvae. We first describe steps for orthotopic xenotransplantation of GSCs into the midbrain of zebrafish larvae, immunofluorescent labeling, and confocal imaging. We then detail procedures for GSC quantification using the Cellpose algorithm. This protocol provides a technique for the semi-automatic segmentation and quantification of human cancer cells in xenograft experiments. With this approach, cancer cell survival and proliferation can be determined in an unbiased manner. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.